Concentrations of escitalopram in blood of patients treated in a naturalistic setting: focus on patients with alcohol and benzodiazepine use disorder - Hart, Xenia Marlene; Heesen, Sebastian H.; Schmitz, Christian N.; Dörfler, Sebastian; Wedekind, Dirk; Gründer, Gerhard; Hiemke, Christoph; Havemann-Reinecke, Ursula (European archives of psychiatry and clinical neuroscience, 2023)
The selective serotonin reuptake inhibitor escitalopram (ESC) is indicated for the treatment of major depressive disorder (MDD) and of generalized anxiety disorder (GAD). Monitoring of blood levels (BLs) is strongly indicated due to ESC’s high interindividual pharmacokinetic variability. The aim of this study was to analyse clinical efficacy and pharmacokinetic influences on ESC BLs, in patients with depressive disorder alone and with comorbid alcohol or benzodiazepine use disorder. Data were collected from patients treated under naturalistic conditions for whom Therapeutic Drug Monitoring (TDM) was requested to guide antidepressant drug therapy and analysed retrospectively. Particular emphasis was given to patients with alcohol or benzodiazepine use disorder. Responders according to the clinical global impression (CGI) scale were compared with nonresponders for their ESC blood level (BL). The patient sample included 344 patients from 16 psychiatric hospitals in Germany. Influencing factors that could explain 22% of ESC BLs were dose, sex and age. Variability was high between individuals, and doses up to 40 mg were common in real-world settings. Patients treated with ESC monotherapy who responded showed a trend towards higher BLs compared to nonresponders with a concentration of 15 ng/mL separating both groups. Pathological changes in liver function (indicated by elevated GGT in combination with an AST/ALT ratio ≥ 1) resulted in higher dose-corrected ESC concentrations. Influencing factors that could explain 22% of ESC blood levels were dose, sex, and age. Our findings confirm the currently recommended lower threshold level and support the need for standard TDM analyses in everyday clinical practice. The ICD 10 diagnosis alcohol dependence alone does not lead to pharmacokinetic changes in the metabolism of ESC, but altered liver function does.